High reactivity of H2O vapor on GaN surfaces - Sumiya, Masatomo; Sumita, Masato; Tsuda, Yasutaka; Sakamoto, Tetsuya; Sang, Liwen; Harada, Yoshitomo; Yoshigoe, Akitaka (Science and technology of advanced materials, 2022)
Understanding the process of oxidation on the surface of GaN is important for improving metal-oxide-semiconductor (MOS) devices. Real-time X-ray photoelectron spectroscopy was used to observe the dynamic adsorption behavior of GaN surfaces upon irradiation of H 2 O, O 2 , N 2 O, and NO gases. It was found that H 2 O vapor has the highest reactivity on the surface despite its lower oxidation power. The adsorption behavior of H 2 O was explained by the density functional molecular dynamic calculation including the spin state of the surfaces. Two types of adsorbed H 2 O molecules were present on the (0001) (+c) surface: non-dissociatively adsorbed H 2 O (physisorption), and dissociatively adsorbed H 2 O (chemisorption) molecules that were dissociated with OH and H adsorbed on Ga atoms. H 2 O molecules attacked the back side of three-fold Ga atoms on the (0001̅) (−c) GaN surface, and the bond length between the Ga and N was broken. The chemisorption on the (101̅0) m-plane of GaN, which is the channel of a trench-type GaN MOS power transistor, was dominant, and a stable Ga-O bond was formed due to the elongated bond length of Ga on the surface. In the atomic layer deposition process of the Al 2 O 3 layer using H 2 O vapor, the reactions caused at the interface were more remarkable for p-GaN. If unintentional oxidation can be resulted in the generation of the defects at the MOS interface, these results suggest that oxidant gases other than H 2 O and O 2 should be used to avoid uncontrollable oxidation on GaN surfaces.